Maternal blood inflammatory marker levels increased in fetuses with ventriculomegaly - Li, Qiang; Ju, Xin-Wei; Xu, Jing; Jiang, Jiuhong; Lu, Chang; Ju, Xing-Da (Frontiers in Human Neuroscience, 2022)
Background: Fetal ventriculomegaly is one of the most common abnormalities of the central nervous system (CNS), which can be significantly identified by brain anomalies prenatally by magnetic resonance imaging (MRI). Aberrant white blood cells (WBCs) levels indicate that the maternal is suffering from the infection. Previous studies have confirmed that prenatal infection can affect fetal brain structure, but there is no research revealed the association between maternal blood parameters with fetal ventriculomegaly until now. Method: We measured the width of the lateral ventricle of 142 fetuses, which were divided into the fetal ventriculomegaly group (n=70) and the normal lateral ventricle group (n=72). We compared maternal blood cell levels between the two groups and investigate potential biomarkers of fetal ventriculomegaly. Results: High levels of maternal WBC and neutrophil levels were observed in fetuses with ventriculomegaly (p<0.001), while lymphocyte percentage, monocytes, NLR and platelet were also increased in the fetal ventriculomegaly group (p=0.033, 0.027, 0.034, and 0.025, respectively). ROC analysis suggested that WBC and neutrophil counts might be useful to distinguish fetuses with enlarged lateral ventricles (AUC=0.688, 0.678, respectively). Conclusion: The current study emphasizes the importance of maternal infection for fetal brain growth, which could provide important information for prenatal diagnosis of CNS anomalies. Future research needs longitudinal analysis and exploration of the influence of maternal blood inflammatory marker levels on fetal brain development.